Afobazole metabolite M-11 inhibits quinone reductase 2 - I. A. Kadnikov; M. V. Voronin; S. B. Seredenin (Фармакокинетика и Фармакодинамика)
Resume. Objective. Inhibition of quinone reductase 2 (NQO2) is a perspective target to achieve neuroprotective effect. Anxiolytic drug afobazole (5-Ethoxy-2-[2-(morpholino)-ethylthio]benzimidazole dihidrochloride) and its main metabolite M-11 (2-[2-(3-oxomorpholin-4-il)-ethylthio]-5-ethoxybenzimidazole hydrochloride) can interact with melatonin dependent regulatory site of NQO2. Previously we have figured that afobazole inhibits NQO2. However, the role of interaction between M-11 and NQO2 is unclear. Aim. To study the effect of M-11 on activity of NQO2. Methods. The influence of M-11 on activity of human recombinant NQO2 (hNQO2) was measured utilizing fluorescent spectroscopy. Results. M-11 inhibits hNQO2 in concentrations of 0.5 and 1.0 mM, decreasing enzymatic reaction velocity on 12 and 24 % respectively. In same concentrations, M-11 is inferior to afobazole. Conclusion. Compound M-11 inhibits NQO2 and can be used to study pharmacological effects of afobazole caused by interaction with regulatory site of enzyme.